Audit of Patient Outcomes after Lichtenstein Hernioplasty for the Repair of Adult Inguinal Hernia (Journal of Surgical Sciences, 2019)
Background: Inguinal hernia repair is one of the most commonly performed surgeries worldwide. While numerous surgical approaches exist to treat inguinal hernias, the Lichtenstein tension-free mesh repair remains the gold standard. This retrospective study is carried out to evaluate the short and long term outcomes of Lichtenstein hernioplasty in the hand of a general surgeon. Patients and Methods: A retrospective analysis of all adult inguinal hernia repair by Lichtenstein method between January .2003 and December 2009 was carried out. The outcome measures were early post-operative complications, incidence of chronic groin pain and recurrence rate. Results: A total of 526 procedures were carried out in 445 adult male patients during the study period. The median age of the patients was 49 years (range, 21-73 years). All patients underwent Lichtenstein hernioplasty under spinal anesthesia. Length of hospital stay was median 2.4 days (range, 1-4 days). Median time to the resumption of normal activities was 8 days (range, 5-1 0 days). Urinary retention was the most frequent early post-operative complication (5.1 6%). Rate of wound infection was acceptable (0.44%). Chronic groin pain was experienced by three patients (0.67%). There was no recurrence observed among the 291 (65.4% of the total) patients who were available after two years of the procedure. Conclusion: The Lichtenstein open tension-free mesh repair of adult inguinal hernia is a safe procedure with least post-operative morbidity and least chance for recurrence. It is a simple technique, quick and. easy to perform without compromising the patient's care and long-term outcome in the hand of an experienced general surgeon.Journal of Surgical Sciences (2012) Vol. 16 (2) : 54-58